Utilização de diferentes métodos para detecção do comportamento endoparasitário em fêmeas ovinas de diferentes grupos raciais - Lourenço, Fábio José (2006)
: Haemonchus contortus and the grade of corresponding packed cell volume in females ovine. 47 females ovine of Santa Inês (n=16), Texel (n=16) and Ile de france (n=15) breeds were used. Inside of each breed, animals were distributed in two groups. The animals received diets with 60% of TDN varying the crude protein (CB) amount in 12% and 16% to treatments 1 (T1) and 2 (T2) respectively. All animals were drenched thirty days before the start of the data collect, which were accomplished biweekly during July of 2005 until March of 2006. It was evaluated the ocular mucous membrane individually of all animals in concordance with which is set down by the Famacha® method, as well as, it was obtained in lab, the packed cell volume value of each animal and fecal egg counts (FEC) of each animal. The packed cell volume value showed a variation along the labor due to the variation of FEC values. In spite of it were not identified differences (p > 0.05) between T1 and T2, differences were detected (p > 0.05) for racial group and interactions between racial group x treatment and racial group x infection endoparasite grade. The balances suggest that the monitoring through the determination of the packed cell volume value is effective to identify animals severely parasitized and that FEC values below 1000 eggs per gram of feces do not request drenches, as well as female ovine of Santa Inês breed present larger endoparasite resistance than females of Texel and Ile de france breeds. It was obtained a correlation of 1:0.7991 of the packed cell volume values and classification by method Famacha® seeking the identification of animals attacked by different anemia grades. The method was efficient to identify animals that need anti-parasitic handling being constituted in a tool of support to identify animals susceptible to the Haemonchus contortus.